2015
DOI: 10.1097/bsd.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the “Pedicle Exposure Technique” for Atlantoaxial Instability Patients With a Narrow C1 Posterior Arch

Abstract: The "pedicle exposure technique" is an effective alternative in patients with the C1 posterior arch measuring <4 mm. In consideration of a high screw entry point on the C1 posterior arch, similar to the C1 posterior arch screw technique, we propose that this new technique can reduce venous plexus and C2 nerve root injury while providing effective biomechanical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
18
0
3
Order By: Relevance
“…Tan et al. [12] in his study also have mentioned the same problem and therefore, exposed the C1 “pedicle” by removing the outer portion that contains approximately 4 mm of long bone of the posterior arch. The posterior arch along the trajectory of the C1 posterior arch screw allowing us to enlarge the height of the screw entry point.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Tan et al. [12] in his study also have mentioned the same problem and therefore, exposed the C1 “pedicle” by removing the outer portion that contains approximately 4 mm of long bone of the posterior arch. The posterior arch along the trajectory of the C1 posterior arch screw allowing us to enlarge the height of the screw entry point.…”
Section: Discussionmentioning
confidence: 95%
“…In order to form the posterior border of the vertebral foramen together with joining and completing the vertebral arch, a lamina projects are backwards and medially from each pedicle so as to complete the triangle of the vertebral foramen [16]. Similar to other pedicles, the connection of the C1 posterior arch and lateral mass conforms to the other vertebral pedicles in their anatomical structure and biomechanics [12]. The C1 pedicle screw placement technique is advantageous compared to inserting the pedicle screw directly into the lateral mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Recent studies suggested 3.5-mm screw in lateral mass and/or posterior arch of the pediatric atlas, paving a base for the atlantoaxial screw fixation in the pediatric population. [7][8][9][10] However, those methods placed venous plexus, nerve root, and vertebral artery injury at risk during the exposure of the C1 lateral mass or/and posterior arch. 11,12 Salvage methods are necessary in case of anatomical variations, traumatic or iatrogenic damage, or vertebral artery protection.…”
mentioning
confidence: 97%